2014
DOI: 10.1016/j.mayocp.2013.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Cardiovascular Health: The Dose Makes the Poison…or the Remedy

Abstract: Habitual light to moderate alcohol intake (up to 1 drink per day for women and 1 or 2 drinks per day for men) is associated with decreased risks for total mortality, coronary artery disease, diabetes mellitus, congestive heart failure, and stroke. However, higher levels of alcohol consumption are associated with increased cardiovascular risk. Indeed, behind only smoking and obesity, excessive alcohol consumption is the third leading cause of premature death in the United States. Heavy alcohol use (1) is one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
260
2
22

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(292 citation statements)
references
References 96 publications
8
260
2
22
Order By: Relevance
“…13 It is well known that alcohol abuse is associated with increased prevalence of hypertension 30 and progressive impairment of LV systolic function, leading to dilated cardiomyopathy and congestive heart failure. 31 Previous studies conducted with conventional echocardiographic technique reported also an association between ethanol consumption and impaired LV diastolic properties in asymptomatic chronic alcoholics. 14,15,32 However, information on the effects of moderate ethanol consumption on LV diastolic filling is limited.…”
Section: Discussionmentioning
confidence: 95%
“…13 It is well known that alcohol abuse is associated with increased prevalence of hypertension 30 and progressive impairment of LV systolic function, leading to dilated cardiomyopathy and congestive heart failure. 31 Previous studies conducted with conventional echocardiographic technique reported also an association between ethanol consumption and impaired LV diastolic properties in asymptomatic chronic alcoholics. 14,15,32 However, information on the effects of moderate ethanol consumption on LV diastolic filling is limited.…”
Section: Discussionmentioning
confidence: 95%
“…[7] было по-казано, что предпочтение потребления пива (умеренное) сопровождается снижением кардиоваскулярного риска, хотя и в меньшей степени, чем предпочтение потребления вина. В то же время ряд исследователей [5,[10][11][12][13] выска-зывают предположение, что кардиопротективными свой-ствами обладает исключительно красное вино либо в силу своего химического состава, либо в силу того, что умерен-ное регулярное потребление красного вина характерно для стран или лиц, соблюдающих более здоровую диету по типу средиземноморской. В метаанализе, проведенном M. Roerecke и J. Rehm [14], сделан вывод, что протективная роль умеренного и низкого потребления алкоголя не может быть признана без проведения дополнительных исследований из-за существенной гетерогенности проведенных работ.…”
Section: Discussionunclassified
“…Кроме этого, имеются сведе-ния, что предпочтение потребления того или иного типа алкогольного напитка связано с социальными фактора-ми, такими как возраст, уровень образования и доходов [15], т.е. причиной может быть не протективное действие алкоголя как такового (что, кстати, отвергают ряд иссле-дователей [13]), а особенности стиля жизни обследован-ных либо химическим составом предпочитаемого напитка [5,[11][12][13].…”
Section: материал и методыunclassified
See 1 more Smart Citation
“…Eligible participants were men or premenopausal women between 18 and 55 years old with type 2 diabetes who were receiving biguanides therapy (metformin), which did not change their medications in the previous three months and who had body fat percentage values higher than 16% for men and 24% for women. The exclusion criteria were tobacco use, consumption of > 50 g/day of alcohol (14), pregnancy or lactation, menopause or postmenopause, regular use of hormones, antiinflammatory medications or other medications that might interfere with outcome measures, recent change (in the previous three months) in the level of physical activity (15) or diet, weight instability (> 3 kg in the previous three months), on a therapeutic diet, dietary allergies or intolerances, cancer, or cardiovascular, renal, or liver disease. Of 102 individuals interested to participate in the study, 55 met the inclusion criteria in the initial screening (via telephone).…”
Section: Subjectsmentioning
confidence: 99%